Analysis of the Social and Economic Impacts of Agricultural Land Conversion into Fish Farming Business in Tanjung Raya District, Agam Regency - Rahmat Firdaus; Rizal Rizal; Febria Rahim; Nil Firdaus; Muhammad Tsaqif Aliva (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
Background. Economic changes in the nagari (traditional village) are driving a shift in land use toward more profitable enterprises. In Tanjung Raya District, Agam Regency, many rice paddies have been converted into fish farming due to economic factors and the year-round availability of water. However, this land conversion brings socio-economic impacts, including both increased income and new business opportunities, as well as the reduction of productive rice fields, which can affect food production and the social life of the village. Purpose. This study aims to analyze the factors driving the community of Tanjung Raya District, Agam Regency, to convert rice farming land into fish farming businesses, as well as to examine the socio-economic impacts of the conversion. Method. The method used is a qualitative approach with data collection techniques through in-depth interviews and observation. Informants were selected using purposive sampling, namely farmers who have converted their land and local community leaders Results. The results show that the main factors driving land conversion are economic factors and natural conditions, particularly the abundant year-round water availability. The positive impacts of land conversion can be seen in increased community income, the growth of new businesses in the fisheries sector, and the rising interest of young people in entrepreneurship. However, negative impacts also exist, including the reduction of productive rice fields, decreased rice production, declining income for supporting agricultural businesses, limited employment opportunities for farm laborers, and the weakening of the community's mutual cooperation (gotong royong) social ties.. Conclusion. The conversion of rice farming land into fish farming provides greater financial profit guarantees. This change has a positive impact on household welfare, business opportunities, and local economic activity, but also brings negative consequences in the form of reduced productive rice fields and decreased local rice production. This has the potential to trigger social conflict due to competition over water. These findings can serve as input for stakeholders in formulating policies so that this process can proceed properly